(untitled) (Mustansiria Dental Journal, 2018)
Destructive forms of periodontal disease can occur in children & adolescents. Proximal caries, gingival inflammation & loss of lamina dura are risk factors in development of alveolar bone loss. This study aims to determine the effect of proximal caries with loss of contact of primary molars on interdental hard tissues using a modified bitewing digital imaging technique .One hundred Iraqi children (7&8 years old) of both sexes were included in this study, half of them having proximal caries in their primary molars & served as study group & the other half served as control. The results showed a significant increase in marginal & interproximal alveolar bone crest height in study group with male predominance. Loss of lamina dura & irregular crestal bone appearance was also evident around primary molars with proximal caries. Non significant relationship was found between gingival inflammation & interdental hard tissues. The results indicated that proximal caries with loss of contact play an important role in development of incipient periodontal disease in children.